Judicial Application of the Theory of Maslahah in Islamic Economic Cases in Indonesia - Mustapa Khamal Rokan; Chuzaimah Batubara; Zulham Zulham (Faculty of Sharia (Islamic Law) at Fatmawati Sukarno State Islamic University Bengkulu, 2025)
This study aims to explain the patterns of the maslahah theory's application in resolving Islamic economic legal disputes by judges in Indonesia. It employs a qualitative approach, relying on primary data collected through questionnaires and in-depth interviews. Questionnaires were distributed to judges of Religious Courts across various regions in Indonesia. At the same time, interviews were conducted directly at five Religious Courts—namely the Religious Courts of Medan, Bandung, Semarang, and Yogyakarta—as well as with a Justice of the Supreme Court. The findings reveal that judges' understanding and application of the maslahah theory in Islamic economic cases remain limited. In many judicial decisions, the standardized contracts used were not initially constructed based on maslahah principles, which subsequently influenced the legal considerations made by judges. The principle of prudence is also not yet fully integrated within the maslahah framework. The challenges to implementing maslahah include limited judicial comprehension of the concept, diverse educational backgrounds that shape varying interpretations, unclear regulations governing Islamic economic law, and low public awareness of the significance of maslahah in Islamic legal reasoning. The academic contribution of this research lies in its empirical mapping of the extent to which the maslahah theory is utilized in the practice of Islamic economic adjudication in Indonesia, along with its proposal of a normative framework to strengthen judicial capacity and reform Islamic economic procedural law based on maqāṣid al-sharī'ah. This study also fills a gap in the literature regarding the intersection between Islamic legal theory and contemporary judicial practice within Indonesia's national legal system